(untitled) (Journal of Oriental Studies, 2017)
This article discusses the features of the application of direct and metaphorical meanings in religious texts and describes their impact on changing rules of law. And also will address the study of the Hanafi legal school of metaphorical meanings in linguistic and semantic and legal directions